High prevalence of porcine circovirus 2, porcine parvovirus, and pathogenic leptospires in mummified swine fetuses in Southern Brazil - Herdt,Geslaine (2019)
ABSTRACT: Modern swine production employs a high degree of technology and is organized in various production stages, in which reproduction is one of the most significant. However, reproductive losses associated to fetal death are still high. Fetal losses, including fetal mummification, may occur at a rate below 1.5% in a sound herd. The causes of fetal death can be very diverse, and include various infectious agents. Therefore, investigating the causes of fetal losses is important in the decision-making process related to the control and prophylaxis of the herd. The goal of this study was to carry out a molecular survey, analyzing porcine circovirus 2 (PCV2), porcine parvovirus (PPV), and pathogenic Leptospira as potential agents related to fetal death in swine farms in Southern Brazil. We collected samples from three farms with a mummified index ≥ 2.5%. Fragments of brain, lung, kidney, liver, and heart were sampled for PCR analysis. Out of 100 samples examined, 87, 68, and 22 were positive for PCV2, PPV, and Leptospira spp., respectively. Moreover, we also identified coinfections with two and three pathogens in the same sample. Our findings contribute to the spreading of scientific knowledge related to infectious causes (PPV, PCV2, and pathogenic leptospires) of fetal losses in swine, as evidenced by the high frequencies of the investigated agents.